Phylogeny of Leontopodium (Asteraceae) in China—with a reference to plastid genome and nuclear ribosomal DNA - Xu, Xue-Min; Wei, Zhen; Sun, Jun-Zhe; Zhao, Qing-Fei; Lu, Yang; Wang, Zhen-Long; Zhu, Shi-Xin (Frontiers in Plant Science, 2023)
The infrageneric taxonomy system, species delimitation, and interspecies systematic relationships of Leontopodium remain controversial and are very complex. However, few studies have focused on the molecular phylogeny of this genus. In this study, the characteristics of 43 chloroplast genomes of Leontopodium and its closely related genera were analyzed. Subsequently, the phylogenetic relationships were inferred based on chloroplast genomes and nuclear ribosomal DNA (nrDNA). Finally, together with morphological characteristics, the relationships within Leontopodium were identified and discussed. The results showed that the chloroplast genomes of Filago, Gamochaeta, and Leontopodium were well conserved in terms of gene number, gene order, and GC content. The most remarkable difference among the three genera was the length of the complete chloroplast genome, large single-copy region, small single-copy region, and inverted repeat region. In addition, the chloroplast genome structure of Leontopodium exhibited a high consistency and was obviously different from that of Filago and Gamochaeta in some regions, such as matk, trnK (UUU)-rps16, petN-psbM, and trnE (UUC)-rpoB. All of the phylogenetic trees indicated that Leontopodium was monophyletic. With the exception of the subgeneric level, our molecular phylogenetic results were inconsistent with the previous taxonomy system, which was based on morphological characteristics. Nevertheless, we found that the characteristics of leaf base, stem types, and carpopodium base had phylogenetic correlation and may have potential value in the taxonomic study of Leontopodium. In the phylogenetic trees inferred using complete chloroplast genomes, subgen. Leontopodium was divided into two clades (Clade 1 and 2): most species in Clade 1 had herbaceous stems, amplexicaul or sheathed leaves, and constricted carpopodium; most species in Clade 2 had woody stems, not amplexicaul and sheathed leaves, and not constricted carpopodium.